Effects of perfluorooctanoic acid on stem Leydig cell functions in the rat. (July 2019) - Lu, Hemin; Zhang, Huishan; Gao, Jie; Li, Zhaohui; Bao, Suhao; Chen, Xianwu; Wang, Yiyan; Ge, Renshan; Ye, Leping
Abstract: Perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic (PFOS) are two perfluorinated chemical products widely existing in the environment. Evidence suggested that PFOA might relate to male reproductive dysfunction in rats and humans. PFOA exposure inhibited the function of Leydig cells. However, it is still unknown whether PFOA affects stem Leydig cells (SLCs). In the present study, we examined the effects of a short-term exposure to PFOA on Leydig cell regeneration and also explored the possible mechanism involved. Thirty-six adult Sprague-Dawley rats were randomly divided into three groups and intraperitoneally injected with a single dose of 75 mg/kg ethane dimethyl sulfonate (EDS) to eliminate all Leydig cells. From post-EDS day 7, the 3 group rats received 0, 25 or 50 mg/kg/day PFOA (n = 12 per group) for 9 consecutive days. Exposure to PFOA significantly decreased serum testosterone levels by day 21 and day 56 post-EDS treatment. Also, the expression levels of Leydig cell specific genes (Lhcgr, Scarb1, Star, Cyp11a1, Hsd3b1, Hsd11b1 and Cyp17a1) and their protein levels were all down-regulated. PFOA exposure may also affect proliferation of SLCs or their progeny since the numbers of PCNA-positive Leydig cells were reduced by post-EDS day 21. These in vivo observations were also confirmed by in vitro studies where the effects of PFOA were tested by culture of seminiferous tubules. In summary, PFOA exposure inhibits the development of Leydig cells, possibly by affecting both the proliferation and differentiation of SLCs or their progeny. Graphical abstract: Image 1 Highlights: PFOA affects Leydig cell regeneration in adult rat testis. PFOA affects stem Leydig cell differentiation at environmental-relevant dose. PFOA affects stem Leydig cell proliferation and differentiation. PFOA affects steroidogenic pathway genes and proteins. Abstract : Exposure to perfluorooctanoic acid inhibited Leydig cell regeneration process in adult rats by interfering with stem Leydig cell functions.